Sources of trace metals in PM10 from a petrochemical industrial complex in Northern Mexico - FLORES RANGEL, ROSA MARIA (SPRINGER, 2017)
Concentrations, sources, and relative contributions of Cd, Cr, Cu, Fe, Mn, Pb, Ni, Ti, V, and Zn observed in PM10 in the petrochemical industrial zone of Altamira in Northern Mexico are reported for the first time. Results show that oil refining, alloys, fertilizer, mining, metallurgical processes, and steel production industries are important contributions to PM10 and metal concentrations. PM10 concentrations ranged from 21 to 92 mu g m(-3) and exceeded the revised 24-h average Mexican standard NOM-025-SSA1-2014 of 75 mu g m(-3) 12 % of the study period. The highest metal concentrations were Fe (1.64 mu g m(-3)), Mn (0.57 mu g m(-3)), and Ti (0.29 mu g m(-3)) and were associated with two dominant wind directions. Ti and Fe were associated with NNW winds (natural sources), and Mn and Fe were associated with SSW winds (ferromanganese industry). An average V/Ni ratio of 8.5 was found in this study with highest ratios associated to two dominant wind directions, NNW-NW and SE-SSE, suggesting origins from a fuel oil thermoelectric power plant and a refinery fuel oil, respectively. Pb was associated with industrial activity and never exceeded the Mexican standard of 1.5 mu g m(-3) in 24 h. Zn and Cd were correlated with a dominant easterly wind, suggesting the presence of vehicle exhaust pollutants. The study of the size and shape of PM10 particles by scanning electronic microscopy and energy-dispersive spectroscopy (SEM-EDS) allowed us to confirm the presence of trace metals associated to natural soils and clays, combustion, and industrial processes. The results presented here constitute the first efforts to evaluate toxic metals in a heavily industrialized area in Mexico and can be used to develop air quality management programs.
Keywords: Altamira; Crustal enrichment factors; ICP-OES; Mexico; PM10; Principal component analysis; Trace metals; AIRBORNE PARTICULATE MATTER; EXPLORATORY FACTOR-ANALYSIS; CHEMICAL-COMPOSITION; SOURCE APPORTIONMENT; ATMOSPHERIC AEROSOL; SIZE DISTRIBUTIONS; TOXIC ELEMENTS; SOURCE ORIGIN; HEAVY-METALS; PARTICLES